UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA KELAS VII B SEMESTER 2 PADA MATA PELAJARAN IPS MELALUI PENERAPAN METODE JIGSAW DI SMP NEGERI 6 KOTABARU - Mayawati Mayawati (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2022)
The aim of this research is to determine whether the implementation of cooperative learning model of JIGSAW with audio visual media with the material study IPS can increase interest and learning achievement in the history of class VIIB second semester at public school 6 Kotabaru. This research is a Clasroom Action Research consists of two different cycles with the stages of planning, implementation, observation and reflection. The subjects were VII B class SMPN 6 Kotabaru as many as 30 students. Data collection technique used tests, observation, documentation, questionnaires and field notes. Data analysis technique used is descriptive qualitative analysis techniques. Application of JIGSAW cooperative learning model is able to increase the interest and learning achievement because it provides an opportunity for students to think critically about a subject matter and find a concept directly from the analysis. Students are involved in the process of discovery, which is pushing to build a progressive conceps through the experience of JIGSAW. This learning model is suitable for the material IPS. Keywords: JIGSAW cooperative learning, Students interest, learning achievement and learning motivations